Intervensi Untuk Melatih Social Skill Pada Individu Dengan Disabilitas Intelektual: Literature Review - Larashati; Iftita Rahmi; Yuha Ilayya; Widya Maharani; Reihan Luthviansyah Adhani (PT. Hasba Edukasi Mandiri, 2026)
Intellectual disability is characterized by significant limitations in intellectual functioning and adaptive behavior that manifest before the age of 18. One of the main challenges faced by individuals with intellectual disabilities is difficulty in developing social skills, which affects their ability to interact, build relationships, and adapt to social environments. This study aims to identify and analyze various forms of effective interventions to improve social skills in individuals with mild intellectual disabilities. The method used is a systematic literature review of nine scientific articles selected from the Google Scholar and Semantic Scholar databases, with a publication range from 2015 to 2025. The results of the review indicate that various intervention approaches have proven effective, including Behavioral Social Skill Training (BSST), play therapy, video modeling, the use of mobile applications, peer-mediated interventions, inclusive learning environments, and psychodrama training. All of these approaches rely on the principles of positive reinforcement, modeling, and repeated practice to shape adaptive social behavior. Although their effectiveness has been demonstrated, the implementation of these interventions still faces challenges, such as difficulties in generalizing skills to real-life situations, limited resources, and variations in participants’ motivation and engagement. These findings highlight the importance of employing diverse, personalized intervention approaches and involving the active roles of families and teachers to achieve optimal outcomes. This study is expected to serve as a foundation for developing more flexible and contextual social intervention models in Indonesia.